2005
DOI: 10.1017/s0266467405002300
|View full text |Cite
|
Sign up to set email alerts
|

Vertical stratification of leaf-beetle assemblages (Coleoptera: Chrysomelidae) in two forest types in Panama

Abstract: To study vertical gradients of arthropod species richness in tropical forests, adult chrysomelids were surveyed with similar sampling effort by beating in four plots of 0.8 ha, representative of the canopy and understorey of one wet and one dry forest in Panama. Samples included in total 4615 individuals representing 253 species, and were of similar species richness at the two study sites. At both sites, chrysomelids were significantly more species-rich in the canopy than in the understorey. The proportion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 17 publications
4
51
1
3
Order By: Relevance
“…These patterns are likely to reflect the specific biology of the species concerned and may even change with season (Devries & Walla 2001), although we have not addressed this possibility here. Our finding that there was vertical stratification in the beetle assemblage concurs with those for other tropical forest insect taxa (Longino & Nadkarni 1990;DeVries et al 1997;Brü hl et al 1998;Rogers & Kitching 1998;Basset et al 2001;Schultze et al 2001;Tanabe 2002;Charles & Basset 2005).…”
Section: Discussionsupporting
confidence: 89%
“…These patterns are likely to reflect the specific biology of the species concerned and may even change with season (Devries & Walla 2001), although we have not addressed this possibility here. Our finding that there was vertical stratification in the beetle assemblage concurs with those for other tropical forest insect taxa (Longino & Nadkarni 1990;DeVries et al 1997;Brü hl et al 1998;Rogers & Kitching 1998;Basset et al 2001;Schultze et al 2001;Tanabe 2002;Charles & Basset 2005).…”
Section: Discussionsupporting
confidence: 89%
“…Differences in the community structure of many rain forest organisms (Orians 1969;Pearson 1971;Smith 1973;Terborgh 1980;Bernard 2001;Vieira and Monteiro 2003;Charles and Bassett 2005;Roisin et al 2006) are driven by the marked contrasts in forest structure, lighting, and microclimate observed across strata (Allee 1926;Longman and Jenik 1974;Richards 1996;Madigosky 2004). Because the canopy has a two-dimensional surface with large vertical discontinuities and horizontal gaps created by treefalls (Terborgh et al 1990;Daly and Mitchell 2000), it receives greater amounts of light and experiences more variation in light intensity than do the shaded lower strata (Endler 1993;Walther 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in tropical forests have reported that the abundance and species diversity of lepidopteran (e.g., Basset 2001;Basset et al 2001) and coleopteran (e.g., Basset 2001;Charles and Basset 2005) assemblages are greater in the canopy than in the understory, although there are cases in which the understory layer is as speciose as the canopy layer for Lepidoptera (e.g., Schulze et al 2001;Beck et al 2002) and Coleoptera (e.g., Stork and Grimbacher 2006). In several studies in the tropics, patterns among the various components of diversity are divergent.…”
Section: Discussionmentioning
confidence: 99%